2018
DOI: 10.1021/acssynbio.8b00274
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Reaction Cascade Implemented by Colocalization of Two Proteins within Catalytically Active Inclusion Bodies

Abstract: In nature, enzymatic reaction cascades, i.e., realized in metabolic networks, operate with unprecedented efficacy, with the reactions often being spatially and temporally orchestrated. The principle of "learning from nature" has in recent years inspired the setup of synthetic reaction cascades combining biocatalytic reaction steps to artificial cascades. Hereby, the spatial organization of multiple enzymes, e.g., by coimmobilization, remains a challenging task, as currently no generic principles are available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(111 citation statements)
references
References 81 publications
4
107
0
Order By: Relevance
“…However, presumably due to the lack of an inherent organized structure, only marginal improvements were reported when this approach was used for other metabolic pathways (Horn & Sticht, 2015; Lee, DeLoache, & Dueber, 2012; Young et al, 2017). Interestingly, functional inclusion bodies can retain the catalytic activity of enzymes and play a unique role in the process of biocatalysis, such as excellent stability and recoverability in aqueous or micro‐aqueous organic solvent systems (Diener et al, 2016; Jäger et al, 2018; Kloss et al, 2018a). Herein, whole‐cell catalysis shows that the fusion of SPFH and enzyme could significantly improve the conversion rate of products and effectively reduce the generation of intermediate products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, presumably due to the lack of an inherent organized structure, only marginal improvements were reported when this approach was used for other metabolic pathways (Horn & Sticht, 2015; Lee, DeLoache, & Dueber, 2012; Young et al, 2017). Interestingly, functional inclusion bodies can retain the catalytic activity of enzymes and play a unique role in the process of biocatalysis, such as excellent stability and recoverability in aqueous or micro‐aqueous organic solvent systems (Diener et al, 2016; Jäger et al, 2018; Kloss et al, 2018a). Herein, whole‐cell catalysis shows that the fusion of SPFH and enzyme could significantly improve the conversion rate of products and effectively reduce the generation of intermediate products.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing different types of domains with aggregation tendency is essential to enhance cascade biocatalysis efficiency by functional inclusion bodies in metabolic engineering. In addition, the reported catalytic reactions of functional inclusion bodies are done in vitro (Jäger et al, 2018; Kloss et al, 2018a), but if functional inclusion bodies can directly play a cascade effect in living cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as early as 1989, Worrall and Goss found that IBs of beta-galactosidase contain correctly folded proteins, and the enzyme activity in the IBs is one-third that of soluble galactosidase [48]. In recent years, catalytically active inclusion bodies (CatIBs) formed by fusion of the target enzyme and the coiled-coil domain or aggregation-prone protein have been proposed [49][50][51][52][53][54]. CatIBs represent a promising new form of carrier-free enzyme immobilization, and might have important implications for protein aggregation in vitro or in vivo.…”
Section: Enzyme Aggregation Guided By Active Inclusion Bodiesmentioning
confidence: 99%